KESIAP SIAGAAN MASYARAKAT DALAM PENANGGULANGAN BANJIR DI KOTA SEMARANG - Findayani, Aprilia (Jurnal Geografi, 2015)
Flood disaster, by number and economic losses, account for about a third of all natural catastrophes throughout theworld. Semarang, as a waterfront city has been suffering from floods since historic time. This research aims to capturepeopleâs perception and response to two different kind of flood. The study focused to identify and analyze communityresponse and its relation to their knowledge, preparedness and action level. An exploratory case study based onprimary and secondary data. The primary data were collected through observational study, questionnaires, semistructured interviews, and FGDs. A sample size of 128 was chosen based on purposive sampling methods. The findingsof the study indicated that people in the coastal areas have a high level of knowledge about floods (64%). Thisknowledge is comparatively high on amount of their past experiences of floods; however they lack in preparedness(43%) because most of the residents are fishermen who have low income so they could not must much effort to adapttheir building to flood. On the other hand, people in the inland, they lack in knowledge (18%) because flood iscomparatively recent in their area; but they have a good level of preparedness (24%) because they belong to high andmiddle level income strata. Furthermore, both communities in the coastal area and inland have a high level of actionbecause of a high knowledge and experience for coastal residents and a good preparedness for inland residents. Thisresearch leads to recommendation to improve the adaptive capacity of the people to cope with the floods. Therecommendation is to develop Community-based Disaster Education (CBDE) Framework with the main purpose is toincrease community knowledge about disaster and to enhance community resilience to flood.